Difference in The Influence of Practice Regulating Passes and Regulating The Game Against The Accuracy of Passing in Junior Football Players - Marshal Ahmad Sibarani; Jack Suman Rulis Manurung (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2021)
This research aims to find out what exercises are more influential between the practice of regulating passes and the practice of regulating the game against the accuracy of passing in football games in The Extracurricular Students of Private Elementary School Al Wasliyah 30 Martubung Medan In 2021. Participants in this study as many as 20 students with an age range of 10-12 years. Research design is pre-test two group experimental design. This research instrument is a test of passing accuracy in a piece of football. Quantitative descriptive analysis of data, by comparing differences in pretest and postest results. The results of the study in the form of analysis of two research hypotheses. Analysis of the first hypothesis of pre-test data and post-test accuracy of passing ball pass exercise group according obtained thitung = 6.86. From the list of distributions t using the odds of 1-1/2? = 0.975 with degree of freedom (df) n-1 = 9 obtained tcount (0.975) = 2.26. In the hypothesis testing criteria it is stated that in tcount >ttable with ? = 0.05 then Ho accepted Ha rejected. Analysis of the second hypothesis of pre-test data and post-test accuracy of passing ball of the Set Passen exercise group obtained tcount = 5.43. From the list of distributions t using the odds of 1-1/2? = 0.975 with df n-1 = 9 obtained the price t (0.975) = 2.26. In the hypothesis testing criteria it is stated that in tcount >tcount with ? = 0.05 then Ho rejected Ha accepted. Then it can be concluded by using the form of practice of regulating passes and arranging the game can improve the accuracy of passing in football games in The Private Elementary School Football Extracurricular Student Al Wasliyah 30 Martubung Medan Year 2021. This research contributes to subsequent research by being able to use other variables as treatment in the accuracy of football passing. Keywords: Passing, Game, Passing, Accuracy